Thong-Bhitongan: Development of Educational Media based on Ethnomatematics of Madura Coastal Culture - Tita Tanjung Sari (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study is aimed to develop mathematics learning media inspired by the typical games of the coastal communities of Sumenep Madura Regency. We provide the media with "Thong-Bhitongan" which is defined as a counting tool in Indonesian. This development uses a development design adapted from Thiagarajan, which consists of a definition, design, and development. "Thong-Bhitongan" is a concrete media that students can play with. The validation results of the "Thong-Bhitongan" media were 82.5, and the material validation was 85. Product trials were carried out at three target schools of Kampus Mengajar 4: Duko II Elementary School, Guluk-guluk II Elementary School, and Guluk-guluk IV Elementary School. The results of the product trials showed that the "Thong-Bhitongan" learning media developed was effective in helping to increase students' understanding of numeracy material, as evidenced by the post-test results which were better than the pre-test results and had exceeded the minimum completeness score. In addition, the media "Thong-Bhitongan" also achieved a good response from students. It is expected that the product of this research, namely the mathematics learning media "Thong-Bhitongan" will become an alternative medium in improving students' nomural abilities.